Narración y relatos sobre los vencidos en el medio digital - Francisco Sevillano (Cahiers de Civilisation Espagnole Contemporaine)
The purpose of this paper is to analyze the way in which the discourses and practices of the new social movements are related to the recovery of historical memory in Spain, especially since 2000. The proposed thesis is that digital media (such as show the use of websites and resources such as documentary images, among others) are fundamental vectors in taking the recovery of personal and collective memory towards a new sensitivity to the past, establishing a different relationship with history. Thus, the public use of history around the identity of the victims, their memory and legal reparation is expressed in a new narration «from below» about the recent past of Spain.